2016
DOI: 10.1120/jacmp.v17i5.6291
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive dosimetric planning comparison for early‐stage, non‐small cell lung cancer with SABR: fixed‐beam IMRT versus VMAT versus TomoTherapy

Abstract: Volumetric‐modulated arc therapy (VMAT) is emerging as a leading technology in treating early‐stage, non‐small cell lung cancer (NSCLC) with stereotactic ablative radiotherapy (SABR). However, two other modalities capable of delivering intensity‐modulated radiation therapy (IMRT) include fixed‐beam and helical TomoTherapy (HT). This study aims to provide an extensive dosimetric comparison among these various IMRT techniques for treating early‐stage NSCLC with SABR. Ten early‐stage NSCLC patients were retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 29 publications
3
19
0
Order By: Relevance
“…SABR is an effective treatment for patients with severe complications or pulmonary function who are unable to tolerate surgery. Using 4D‐CT and daily CT simulation to confirm the position and reduce deviation, SABR can deliver a high biological effective dose (BED) to the target while minimizing toxicity to the surrounding normal tissue, which may translate into improved LC and survival rate . With the progress of radiotherapy technology, SABR can be used to treat central lung cancer and even ultracentral lung cancer, which used to be risky to treat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SABR is an effective treatment for patients with severe complications or pulmonary function who are unable to tolerate surgery. Using 4D‐CT and daily CT simulation to confirm the position and reduce deviation, SABR can deliver a high biological effective dose (BED) to the target while minimizing toxicity to the surrounding normal tissue, which may translate into improved LC and survival rate . With the progress of radiotherapy technology, SABR can be used to treat central lung cancer and even ultracentral lung cancer, which used to be risky to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Using 4D-CT and daily CT simulation to confirm the position and reduce deviation, SABR can deliver a high biological effective dose (BED) to the target while minimizing toxicity to the surrounding normal tissue, which may translate into improved LC and survival rate. 10,16,17 With the progress of radiotherapy technology, • ≥Grade 2 radiation pneumonitis: 13.4%, 5.5%…”
Section: Discussionmentioning
confidence: 99%
“…The study by Xhaferllari et al . 27 provided an extensive dosimetric planning among fixed-beam IMRT, VMAT, and TOMO for early-stage NSCLC with SABR. The results demonstrated that VMAT had the optimal trade-off in dose conformity, sparing normal tissue, and treatment efficiency when compared with fixed-beam.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study conducted by Xhaferllari et. al [23], VMAT is dosimetrically advantageous in treating early-stage NSCLC with SABR compared to fixed-beam IMRT, while providing significantly shorter treatment times. Moreover, they pointed out that no significant difference was observed in the two VMAT techniques (SmartArc (SA) and RapidArc (RA)).…”
Section: Plan Comparisonmentioning
confidence: 99%
“…No studies dig into the SIB and conventional prescription VMAT plans. As it is widely known that VMAT is superior to IMRT in dosimetric aspect [23], our study focus on this two type prescription in VMAT plans. SIB-VMAT plans Zhang et al [24], the heart dose-volume parameters of V 5 and V 30 were independent predictors for both cardiac events and overall survival among patients with NSCLC.…”
Section: Plan Comparisonmentioning
confidence: 99%